KONSERVASI BERBASIS KOMUNITAS RELIGI: MEMBEDAH PERAN ORMAS KEAGAMAAN DALAM UPAYA MELESTARIKAN SUMBER DAYA ALAM DI INDONESIA - Ulil Amri (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2012)
This article describes the role of religious-based communities in promoting conservation practices. The subjects of research are pesantrens and schools, which af?liated with Nahdlatul Ulama and Muhammadiyah, the two biggest and oldest Islamic communities in Indonesia. The idea of conservation is originated from a combination of ethical values based on global environmental movement and the Islamic eco-theology. This idea is manifested into three types of practices including: 1) mitigating environmental destructive activitiesmainly deforestation; 2) conducting reforestation; and 3) providing alternative energy resources. Despite their relative success in introducing conservation practices, there are some obstacles that may hamper the future of such practices, i.e. the problem of elite capture, lack of initiative from community members, different views which leads to con?ict, and half-hearted commitment of certain community members to support the conservation practices.Keywords: Konservasi, Komunitas Religi, Nahdatul Ulama, Muhammadiyah